Building a predictive model for assessing the risk of Salmonella shedding at slaughter in fattening pigs - Bernad-Roche, María; Marín-Alcalá, Clara María; Cebollada-Solanas, Alberto; de Blas, Ignacio; Mainar-Jaime, Raúl Carlos (Frontiers in Microbiology, 2023)
Salmonellosis continues to be a major cause of foodborne outbreaks worldwide and the pig, one on the main sources of human infection. Salmonella pork contamination is a major concern for abattoirs, and it relates to the presence of Salmonella in the pigs’ feces at slaughter. Being able to predict the risk of shedding Salmonella of pigs arriving at the slaughterhouse could help to mitigate abattoir and carcass contamination. For this purpose, 30 batches of 50 pigs each from 30 different fattening units were selected. Pigs were tagged and bled for detection of antibodies against Salmonella approximately one month before slaughter. Pooled floor fecal samples from 10 pens per unit were also collected for Salmonella detection and a questionnaire on biosecurity administered to each farm. At the abattoir, colon content was collected from each tagged pig for Salmonella shedding assessment. A predictive model for Salmonella shedding at slaughter was built with 2/3 of the pigs by means of random-effects logistic regression analysis, where Salmonella shedding was the dependent variable, and pig serology and other farm/environmental characteristics were included as the independent ones. The model included farm as the grouping factor. Data from the remaining 1/3 of the pigs were used for model validation. Out of 1,500 pigs initially selected, 1,341 were identified at the abattoir and analyzed. Salmonella was detected in 13 (43.3%; 95%CI= 27.4-60.8) of the fattening units. Mean batch seroprevalence (cut-off OD%≥40) among the fattening units was 31.7% (95%CI= 21.8-41.0), and a total of 316 pigs (23.6%; 95%CI= 21.4-25.9) shed Salmonella at slaughter. The model predicted reasonably well (Area Under the Curve= 0.76; P<0.05) whether a pig would shed Salmonella at slaughter, with estimates of sensitivity and specificity of 71.6% and 73.6% respectively. Serology, the percentage of Salmonella-positive pens in the farm, and the internal biosecurity score were significantly associated (P<0.05) with Salmonella shedding at the abattoir, and several scenarios were observed according to the model. The study highlighted that although serology may be helpful to identify batches of pigs at risk of shedding Salmonella upon their arrival to the abattoir, in some scenarios it may not be necessary.